2007
DOI: 10.1038/sj.ijir.3901564
|View full text |Cite
|
Sign up to set email alerts
|

Long-term changes in sympathetic innervation in the corpus cavernosum of the STZ-diabetic rat

Abstract: The noradrenaline (NA) concentration in the rat corpus cavernosum (CC) increased to approximately 350% of control values after about 8 weeks of hyperglycaemia induced by the intraperitoneal injection of streptozotocin (STZ) at 10 weeks of age. These changes were maintained for at least a further 32 weeks of hyperglycaemia and occurred without any significant change in the weight in the tissue. Smaller but significant increases in NA concentration occurred in the glans penis (GP) reaching 150-175% of the contro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2008
2008
2014
2014

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 35 publications
1
7
0
Order By: Relevance
“…This same study, and a second (Yagihashi and Sima, 1986), also examined the DNP in STZ-treated rats and reported axonal shrinkage and axonal accumulations of glycogen. Abnormally dilated nerve fibers and engorged endings of autonomic nerves were described in rat penile shaft after 5–8 months of HG (Morrison et al, 2007a,b), corresponding to the time scale of severe neuropathy in our recordings. The lack of change in morphology of MPG and proximal CN, and limited abnormalities in distal segments of CN presented in our findings and previous histological evaluations, suggest the prevalence of functional, but not structural, HG-induced alterations in CN.…”
Section: Discussionsupporting
confidence: 58%
“…This same study, and a second (Yagihashi and Sima, 1986), also examined the DNP in STZ-treated rats and reported axonal shrinkage and axonal accumulations of glycogen. Abnormally dilated nerve fibers and engorged endings of autonomic nerves were described in rat penile shaft after 5–8 months of HG (Morrison et al, 2007a,b), corresponding to the time scale of severe neuropathy in our recordings. The lack of change in morphology of MPG and proximal CN, and limited abnormalities in distal segments of CN presented in our findings and previous histological evaluations, suggest the prevalence of functional, but not structural, HG-induced alterations in CN.…”
Section: Discussionsupporting
confidence: 58%
“…In a recent study using STZ diabetic rat, the CC displayed 350% NA concentration over control values at 8 weeks (Morrison et al. , 2007).…”
Section: α‐Adrenoceptors Endothelin‐i and The Rho‐kinase Pathwaymentioning
confidence: 98%
“…However, whether this effect of STZ-induced diabetes involves an increase in the number of axons within the nerve fibers was not resolved. Other studies have indicated that STZ-induced diabetes stimulates growth of sympathetic nerve terminals in the heart (Felten et al, 1982), corpus cavernosum (Morrison et al, 2007), and seminal vesicle (Morrison et al, 2006). In both corpus cavernosum and seminal vesicle, the TH-IR of the nerve fibers was increased (Morrison et al, 2006, 2007).…”
Section: Discussionmentioning
confidence: 98%
“…Other studies have indicated that STZ-induced diabetes stimulates growth of sympathetic nerve terminals in the heart (Felten et al, 1982), corpus cavernosum (Morrison et al, 2007), and seminal vesicle (Morrison et al, 2006). In both corpus cavernosum and seminal vesicle, the TH-IR of the nerve fibers was increased (Morrison et al, 2006, 2007). In addition, STZ-induced diabetes increased the NPY content of both the corpus cavernosum and seminal vesicle (Morrison et al, 2009).…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation